Direct Synthesis of Benzofuro[2, 3‐b]pyrroles through a Radical Addition/[3, 3]‐Sigmatropic Rearrangement/Cyclization/Lactamization Cascade. Issue 22 (27th March 2014) - Ueda, Masafumi; Ito, Yuta; Ichii, Yuki; Kakiuchi, Maiko; Shono, Hiroko; Miyata, Okiko
Abstract A straightforward synthetic method for the construction of benzofuro[2, 3‐b]pyrrol‐2‐ones by a novel domino reaction through a radical addition/[3, 3]‐sigmatropic rearrangement/cyclization/lactamization cascade has been developed. The domino reaction of O‐phenyl‐conjugated oxime ether with an alkyl radical allows the construction of two heterocycles with three stereogenic centers as a result of the formation of two CC bonds, a CO bond, and a CN bond in a single operation, leading to pyrrolidine‐fused dihydrobenzofurans, which are not easily accessible by existing synthetic methods. Furthermore, asymmetric synthesis of benzofuro[2, 3‐b]pyrrol‐2‐one derivatives through a diastereoselective radical addition reaction to a chiral oxime ether was also developed.